INVESTIGASI WABAH KEJADIAN LUAR BIASA (KLB) PENYAKIT CHIKUNGUNYA DI WILAYAH KERJA PUSKESMAS GOGAGOMAN KECAMATAN KOTA MOBAGU BARAT - Yunus, Malik; Sandalayuk, Marselia (LPPM Universitas Hein Namotemo, 2017)
Chikungunya is a disease that comes from alphaviruses that enter the body through the bite of Aedes Albopictus mosquito. People who suffer from chikungunya usually experience symptoms of headache, joint pain and often hot body, so that the patient will experience pain that causes disruption of activity. Chikungunya usually occurs in areas that are densely populated and tropical or subtropical. Because the main vectors of this disease the same as dengue Aedes Aegypti mosquito, the location of the spread was almost the same. In areas likely to be prone to dengue fever it may also be an area prone to chikungunya (Widoyono, 2008). The aim of this research is to know and get an illustration of Chikungunya disease happening in Modayag Community Health Center area. To know the risk factors associated with Cikungungnya in doing research with Case Study - Control. Selection of Research Samples are as follows: Cases are all Cikungungnya sufferers located in two RT Locations in as source and place of transmission, Control is not suffering Cikungungnya. Data analysis was collected with SPSS, presented in table, graph and narration.